Implementation Indonesia EFL Pre-Service Teachers Classroom Strategies in Teaching English and Student Responses in Thai Schools - Ariska, Putri; Ginting, Pirman (Journal of English Language and Education, 2026)
This study aims to examine the effectiveness of role-play strategies implemented by Indonesian pre-service EFL teachers and to investigate students’ responses to English learning at Turkeeyah Tunummah School, Southern Thailand. The research employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The participants consisted of 23 students engaged in an English lesson on the topic “My Daily Activity.” Data were collected through student response questionnaires administered before and after the implementation of the role-play strategy and were analyzed using descriptive statistics and a paired-samples t-test. The findings revealed a statistically significant improvement in student responses following the implementation of the role-play strategy. The mean score increased from 55.48 at the pretest stage to 92.83 at the posttest stage, with a significance level of p 0.05. These results indicate that role-play strategies effectively enhance students’ self-confidence, learning motivation, active participation, and speaking skills within a multilingual and multicultural EFL classroom context.